Explanation and cognition - Keil, Frank C., 1952-; Wilson, Robert A. (Robert Andrew) (MIT Press, 2000)
These essays draw on work in the history and philosophy of science, the philosophy of mind and language, the development of concepts in children, conceptual change in adults, and reasoning in human and artificial systems. Explanations seem to be a large and natural part of our cognitive lives. As Frank Keil and Robert Wilson write, "When a cognitive activity is so ubiquitous that it is expressed both in a preschooler's idle questions and in work that is the culmination of decades of scholarly effort, one has to ask whether we really have one and the same phenomenon or merely different cognitively based phenomena that are loosely, or even metaphorically, related."This book is unusual in its interdisciplinary approach to that ubiquitous activity. The essays address five basic questions about explanation: How do explanatory capacities develop? Are there kinds of explanation? Do explanations correspond to domains of knowledge? Why do we seek explanations, and what do they accomplish? How central are causes to explanation? The essays draw on work in the history and philosophy of science, the philosophy of mind and language, the development of concepts in children, conceptual change in adults, and reasoning in human and artificial systems. They also introduce emerging perspectives on explanation from computer science, linguistics, and anthropology. ContributorsWoo-kyoung Ahn, William F. Brewer, Patricia W. Cheng, Clark A. Chinn, Andy Clark, Robert Cummins, Clark Glymour, Alison Gopnik, Christine Johnson, Charles W. Kalish, Frank C. Keil, Robert N. McCauley, Gregory L. Murphy, Ala Samarapungavan, Herbert A. Simon, Paul Thagard, Robert A. Wilson